The introduction of the automated control system for fare payment with mobile module NFC in public transport - Бойко, Юрій Олександрович (Technology audit and production reserves, 2015)
Automated control system for fare payment is a modern hardware and software tools to increase profitability of passenger traffic and effective way to improve the organization of public transport services. After analyzing the contactless payment system in public transport of the city of Kremenchug, you can say that with the introduction of the system will benefit all participants in the transport process, both passengers and transport companies. Transport companies will be able to monitor the operation of rolling stock, conducts counting the number of passengers to adjust the mode of the drivers on the line routes to improve and optimize the transport network. This system is simple to use by passengers, because having only a mobile phone or smart card can easily pay for travel and control expenses at any time.